2019
DOI: 10.1038/s41467-019-10810-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying entanglement in a 68-billion-dimensional quantum state space

Abstract: Entanglement is the powerful and enigmatic resource central to quantum information processing, which promises capabilities in computing, simulation, secure communication, and metrology beyond what is possible for classical devices. Exactly quantifying the entanglement of an unknown system requires completely determining its quantum state, a task which demands an intractable number of measurements even for modestly-sized systems. Here we demonstrate a method for rigorously quantifying high-dimensional entanglem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 50 publications
2
42
1
1
Order By: Relevance
“…Furthermore, we have certified high-dimensional entanglement up to 48 dimensions in just 140 s, a significant development in quantum information processing with high-dimensional quantum states. While certifying high-dimensional entanglement is now routinely performed using single-outcome projective measurement techniques 34,45,49,50 , these approaches are tedious and prohibitively time-consuming. Our SPAD camera-based technique outperforms these approaches in term of speed and scalability, with a demonstrated speed-up by more than a factor 500× and the potential access to up to 4 × 10 6 two-photon modes ((32 × 64) 2 ) in parallel, indicating a key role to be played in future quantum information processing systems based on highdimensional entanglement.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have certified high-dimensional entanglement up to 48 dimensions in just 140 s, a significant development in quantum information processing with high-dimensional quantum states. While certifying high-dimensional entanglement is now routinely performed using single-outcome projective measurement techniques 34,45,49,50 , these approaches are tedious and prohibitively time-consuming. Our SPAD camera-based technique outperforms these approaches in term of speed and scalability, with a demonstrated speed-up by more than a factor 500× and the potential access to up to 4 × 10 6 two-photon modes ((32 × 64) 2 ) in parallel, indicating a key role to be played in future quantum information processing systems based on highdimensional entanglement.…”
Section: Discussionmentioning
confidence: 99%
“…High-dimensional QFT and compiled modular exponential [42] are applied on twin beams from SPDC, respectively. The optical nonlinear process could provide a large enough state space for further demonstration [25]. Furthermore, our scheme is also available for indistinguishable multi-photon manipulation including boson sampling [18].…”
Section: Extension To Photon Pairsmentioning
confidence: 99%
“…Particularly, spatial mode entanglement induced by spontaneous parametric down conversion (SPDC) in nonlinear crystals [2,3,[20][21][22][23][24] has been well investigated. Two photon spatial entanglement with high Schmidt number is potentially available with meticulously designed pump parameters [16,17,25]. However, the exploitation of such quantum resources has been hindered by the lack of universal operation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, EPR-steering has been understood to make up part of a hierarchy of quantum correlations, situated between entanglement [ 81 , 82 ] and Bell non-locality [ 83 ]. In addition to methods utilizing variance-based URs [ 84 ], entropic URs, such as those in Section 2.2 , can be used to identify EPR-steering [ 85 , 86 ] and to quantify high-dimensional entanglement [ 87 , 88 ]. Some of these URs can be used to test security in continuous variable quantum cryptography [ 89 , 90 ], and it has been shown that violation of entropic EPR-steering criteria are directly related to the secret key rate in one-sided device independent cryptography [ 91 ].…”
Section: Utility Of Uncertainty Relations In Quantum Physicsmentioning
confidence: 99%